Pelaksanaan Layanan Bimbingan dan Konseling di Madrasah Aliyah Negeri 2 Banjarnegara - Permana, Eko Jati (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2015)
This study aims to investigate the implementation of guidance and counseling services conducted in MAN 2 Banjarnegara. This research is a qualitative descriptive study.The participants are the four guidance and counseling teachers selected using purposive sampling techniques. The data collection instrument used an interview guidelines that is supported by interviews recording and documentation. Thi study used Miles and Huberman models as the data analysis techniques. The results showed that the implementation of guidance and counseling services in the MAN 2 Banjarnegara in the form of orientation services, information services , placement and distribution services, tutoring services, individual counseling, group counseling services are in the good category. The results of this study is useful for counseling and guidance teachers as the basis for the development of guidance and counseling services that are effective in accordance with the needs and development of the students.